2002
DOI: 10.1128/jvi.76.8.3605-3614.2002
|View full text |Cite
|
Sign up to set email alerts
|

Replication Fidelity of the supF Gene Integrated in the Thymidine Kinase Locus of Herpes Simplex Virus Type 1

Abstract: Recombinant viruses were constructed to have an Escherichia coli replicon containing a mutagenesis marker, the supF gene, integrated within the thymidine kinase locus (tk) of herpes simplex virus type 1. These viruses expressed either wild-type or mutant DNA polymerase (Pol) and were tested in a mutagenesis assay for the fidelity of their replication of the supF gene. A mutation frequency of approximately 10 ؊4 was observed for wild-type strain KOS-derived recombinants in their replication of the supF gene. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…Figure 1 illustrates the supF mutagenesis assays used for the study of HSV-1 replication fidelity. Studies of recombinant viruses derived from the HSV-1 KOS strain and the transient replication assay using the modified shuttle plasmid have revealed that the KOS virus replicates the supF genes at a mutation frequency (Hwang, Liu, and Hwang, 2002;Hwang et al, 1999), which is consistent with that observed for the supF amplicon propagated in mammalian cells (Seidman et al, 1985).…”
Section: Supf Mutagenesis Assaysupporting
confidence: 64%
See 4 more Smart Citations
“…Figure 1 illustrates the supF mutagenesis assays used for the study of HSV-1 replication fidelity. Studies of recombinant viruses derived from the HSV-1 KOS strain and the transient replication assay using the modified shuttle plasmid have revealed that the KOS virus replicates the supF genes at a mutation frequency (Hwang, Liu, and Hwang, 2002;Hwang et al, 1999), which is consistent with that observed for the supF amplicon propagated in mammalian cells (Seidman et al, 1985).…”
Section: Supf Mutagenesis Assaysupporting
confidence: 64%
“…Although tk mutants are easily identified in a simple plaque assay, this method may not be sensitive enough to detect all mutants, such as silent mutations and mutations that maintain enzyme activity. It is estimated that the TK mutagenesis assay can detect less than 50% of all possible substitutions of tk mutations (Hwang, Liu, and Hwang, 2002). Despite this, an extensive study (Lu, Hwang, and Hwang, 2002a) of tk mutants derived from wild-type HSV-1 strain KOS found that HSV replicates DNA with a genomic mutation rate similar to those of other DNA-based microbes (Drake and Hwang, 2005).…”
Section: Antiviral Therapy and Emergence Of Resistant Mutantsmentioning
confidence: 99%
See 3 more Smart Citations